Pre-Maxillary Turn over Palatal Flap for Bilateral Cleft Palate Repair - Zahoor Zaidi, Syed Fahad; Padhiar, Waqar Ahmed; Awan, Asadullah; Ullah, Haseeb; Husain, Syed Tahir; Khan, Ihsanullah (Journal of Neonatal Surgery, 2025)
Background: Bilateral cleft palate is a relatively complex repair, and techniques that yield both structural stability and functional results are the best. A promising approach to improve the closure success rate, reduce fistula formation and promote maxillary growth is the premaxillary turnover palatal flap in combination with selective use of the vomer flap. Objective: This study aimed to evaluate the efficacy of the turnover palatal flap technique in achieving stable closure, minimizing complications, and improving functional outcomes, including maxillary growth and speech. Materials and Methods: A study was conducted at the Plastic Surgery Department of Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi from March 2023 to September 2024, involving 63 patients with bilateral cleft palate (average age: 10.2 months). Demographic information, use of preoperative nasoalveolar molding (NAM), and surgical result, complication, maxillary growth and speech outcome were collected by the researchers. Findings included pain and complications recorded during follow up visits and statistical analysis was made to compare outcomes. Results: Successful closure of the turnover flap was obtained in 76.2% of cases with a low fistula formation rate (19%). Surprisingly, speech outcomes were considered good in 36.5 percent of patients. Maxillary growth was normal in 54.0%, and 79.4% had no postoperative complications. Effective pain management was evident from the 71.5% of patients who reported mild to moderate pain. Conclusion: With or without vomer flap reinforcement, the premaxillary turnover palatal flap is applicable in bilateral cleft palate repair and stable closure and favorable functional results. Maxillary growth is supported by the technique together with NAM and comprehensive postoperative care; thus the need for further interventions is reduced